The Winning Strategy and the Risk Management of The Indonesia Navy Defense in Anticipating the VUCA Environment - Arip Supriyadi; Setyoko, Budi (International Research & Development for Human Beings (IRDH), 2025)
The strategic planning and defense systems in Indonesia present a fascinating subject for discussion. The aim of this article is to ensure that all parties involved in defense design are more conscious of the developments within a VUCA (Volatile, Uncertain, Complex, and Ambiguous) strategic environment. This article used the descriptive method with in-depth elaboration analysis. The result shows that developing a grand strategy to achieve victory, several key considerations must be taken are Evaluating risks and uncertainties, Analyzing the distinction between security and safety, Interpreting the concept of victory as encompassing peace, not just success in conflict, Basing effective strategies for addressing threats and vulnerabilities on thorough research, Identifying and addressing threats and vulnerabilities are crucial for maintaining global stability and peace. We have to consider the VUCA environment in making the grand strategy. Volatility refers to a dynamic, non-linear system where causes and effects can lead to imbalances. Uncertainty refers to unpredictable conditions that necessitate Indonesian Navy careful approach in planning defense strategies and determining the appropriate structure for the armed forces. Complexity illustrates the patterns of past events but cannot predict their recurrence. Ambiguity refers to an uncertain situation that requires the Indonesian Navy to be prepared to act if conditions escalate to a more dangerous level than anticipated. The Grand Strategy of the Indonesian Navy Defense must take into account the VUCA Strategic Environment, which encompasses Volatility, Uncertainty, Complexity, and Ambiguity. Understanding the complexity of VUCA is vital as it enhances organizational self-awareness, particularly within the military